Homogenization of electric field distribution facilitating the Zn anode reversibility. Issue 98 (22nd November 2022) - Tang, Han; Liang, Huadong; Jia, Runmin; Liu, Yu; Chen, Huibiao; Luo, Hongyu; Yang, Wei; Wang, Jian; Zhou, Mengjun; Luo, Ping; An, Qinyou
Abstract : Modulating the surface scratches homogenized the deposition electric field and reduced the local current density. The reasonable surface treatment could limit the "tip effect" and bring homogeneous plating and stripping of the Zn electrode. Abstract : The surface morphology of the zinc-metal electrode was modulated using different levels of physical polishing treatment. Modulating the surface scratches homogenized the deposition electric field and reduced the local current density. A reasonable surface treatment could limit the "tip effect" and bring homogeneous plating and stripping of the Zn electrode.